Diverging sub-fields in functional ecology - Viliani, Leonardo; Bonelli, Simona; Gentile, Giorgio; Parile, Enrico; Riva, Federico (Frontiers in Ecology and Evolution, 2024)
The number of studies in functional ecology grew exponentially in the last decades. Whether and how ecologists changed how they conduct these studies, however, remains poorly understood.Using butterflies as a model taxon, we assessed forty years of research asking whether and how functional analyses have changed. We found that how authors contextualize their work corresponds to divergent sub-fields in functional ecology. Articles explicitly referring to "functional traits" have become increasingly common in the last decade, focus on many species, and typically address the relationship between biodiversity and environmental gradients.Meanwhile, articles that do not refer to "functional traits" usually account for variation within species and among sexes and are based on direct measures of the trait of interest. These differences have increased over time, highlighting a schism. As functional ecology continues to grow, authors and syntheses will benefit from awareness of these different schools of thought.